Gender, "race", and class in schooling : a new introduction - Gaine, Chris (Falmer Press, 1999)
"With education and social inequalities under scrutiny, this timely book provides an overview of research and key problems in the field of education and three significant social inequalities - gender, 'race' and social class. It offers both a summary of research into and arguments about the main issues and some of the key changes which are now emerging." "Gender, 'Race' and Class in Schooling examines the issues in turn, but shows the links between them, as one of the constantly emerging themes is that the three inequalities interact."--Jacket